A newer method and its comparison with other available methods in wireless sensor network (International Journal of Engineering and Computer Science, 2017)
The real challenge for wireless sensor network is to design optimal routing protocol which enhance the network lifetime by reducing energy consumption. Energy saving is the main component in designing of network architecture. Many routing protocol have been developed in the past years and research is still going on for the best possible solution .One of the best routing protocols between them is clustering based protocol. It is the most efficient method of reducing energy consumption by load balancing over the nodes. In this thesis, a new routing protocol is proposed to improve network lifetime by reducing energy dissipation. AODV protocol is modified to improve leach protocols transmitting capability, enhancing throughput and reducing packet loss and delay. It had used TDMA MAC protocol for the transmission of data among the nodes and base station. This reduces collision in the channel and provide real time guarantees by eliminating packet losses and delay. Then multi hop routing protocol is used instead of direct transmission as it gives better results in transmission of data. It helps in reducing energy consumption in far away nodes during transmission. .